EIB Working Papers 2019/04 - Can survey-based information help to assess investment gaps in the EU? (Volume 2019/4) - Dejuan, Daniel (European Investment Bank, 2019)
Information from surveys can be used alongside macroeconomic indicators to provide a better understanding of the obstacles to investment faced by firms. This study uses merged firm level data from the European Investment Bank Investment Survey (EIBIS) and hard data from firms' balance sheets and profit and loss information to investigate how well survey results correlate with macro-based hard data. Firms' perceptions of impediments to investment tend to be related to firms' specific characteristics: firms that are smaller, more indebted, less profitable or with less liquidity, tend to report more impediments. Nonetheless, after controlling for firm specific characteristics, the investment gaps reported by firms remain correlated with the reported impediments.